Style and context of old Greek Job - Dhont, Marieke. (Supplements to the Journal for the Study of Judaism, 2017)
In Style and Context of Old Greek Job , Marieke Dhont offers a new understanding of the linguistic and stylistic diversity in the Septuagint corpus. To this end, the author innovatively uses Polysystem Theory, which has been developed in the field of modern literary studies. After discussing the appropriateness of a systemic approach to understanding Jewish-Greek literature, the author reflects on the Jewishness of Greek-language texts. Dhont then presents a thorough literary analysis of the Old Greek version of the book of Job. On this basis, she explains the dynamics that produced the translation of Old Greek Job and its position within the development of a Jewish-Greek literary tradition.